ANALISIS LOGIS DAN EPISTEMOLOGIS ISTINBATH HUKUM BERBASIS ILMU DHARURI DAN NAZHARI - Zainal Pikri; Agustini Agustini (Khazanah: Jurnal Studi Islam dan Humaniora, 2021)
This article explores the construction of the definition of "fiqh" in several books of ushul fiqh of the mutakallimūn school by starting from an exploration of the classification of knowledge in Islamic philosophy and theology. Furthermore, this article identifies the implications of the classification of knowledge in theology, namely ‘ilm dharūrī (immediate knowledge) and ‘ilm nazharī (discursive knowledge) as the basis for the formation of ushul fiqh, with the main focus on the term "fiqh" in several books of ushul fiqh by mutakallimūn. In the final section, this article discusses two logical and epistemological aspects of the nazharī paradigm and analyzes the example of nazharī reasoning in usul fiqh from Al-Amidi in those two aspects. This article argues that logical and epistemological analysis within the nazharī paradigm can identify divine elements and human understanding in the steps producing Islamic law so that the distinction between syariah and fiqh can be clarified systematically.Artikel ini menelusuri konstruksi definisi “fiqh” dalam beberapa kitab ushul fiqh aliran mutakallimūn dengan memulai dari eksplorasi klasifikasi ilmu dalam filsafat Islam dan kalam. Selanjutnya artikel ini mengidentifikasi implikasi klasifikasi ilmu dalam kalam, yaitu ilmu dharūrī dan nazharī sebagai dasar dalam pembetukan ilmu ushul fiqh, dengan fokus utama pada istilah “fiqh” pada beberapa kitab ushul fiqh aliran mutakallimūn. Pada bagian akhir, artikel ini membahas dua aspek logis dan epistemologis dari paradigma ilmu nazharī dan menganalisis contoh penalaran nazharī dalam ushul fiqh dari Al-Amidi dari sisi kedua aspek ini. Artikel ini berargumen bahwa analisis logis dan epistemologis dengan paradigma ilmu nazharī dapat memilah unsur ilahi dan pemahaman manusia dalam langkah-langkah istinbāth hukum Islam sehingga pembedaan antara syariah dan fiqh dapat diklarifikasi secara sistematis.